Histological Analysis of Vascular and Collagen Tissues in the Ventral and Corresponding Dorsal Skin of Mid-Penile Hypospadiac Penis at the Meatal and Coronal Levels: A Comparative Study (Journal of Paediatric Surgeons of Bangladesh, 2013)
Background: Hypospadias where surgery is the only option to correct this birth defect which is usually associated with post-operative urethrocutaneous fistula formation even in best hands. The site of fistula is mostly at coronal level (80%) and less common at meatal level. Many factors are supposed to be responsible for causation of this fistula, important one is the developmentally defective ventral penile skin at and / or distal to the urethral meatus where some local healing factors like vascular and collagen tissues are insufficient. Objective: To determine histologically whether the ventral skin of hypospadiac penis at the meatal and coronal levels differ from the corresponding dorsal skin levels in terms of vascular and collagen tissue. Study design: Observational comparative study. Place of study: (1) Department of Paediatric Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka. Period of study: December 2008 to 15 May 2010. Materials & Methods: A total of 10 patients with mid-penile hypospadias without chordee were included in this study. Representative skin tissues were collected from ventral skin and corresponding dorsal skin of the meatal and coronal levels of every patient. Haematoxylin-eosin stained slides were prepared from each tissue specimen and were examined under microscope to determine the differences in blood vessels and collagen tissues distribution. Paired t test was used to test the significance of differences. Results: Significantly lower proportion of sectioned blood vessels was found in the ventral skin than in the dorsal skin at the coronal level. The proportion of sectioned collagen fibre bundles was also significantly lower in the dorsal skin than in the ventral skin at the coronal level. Conclusion: This study reveals difference in distribution of blood vessels and collagen fibre bundle in the ventral skin in comparison with corresponding dorsal skin of hypospadiac penis at meatal and coronal levels. DOI: http://dx.doi.org/10.3329/jpsb.v2i1.15158 Journal of Paediatric Surgeons of Bangladesh (2011) Vol. 2 (1): 17-21